Productivity and composition of grapes and wine of vines intercropped with cover crops Produtividade e composição de uva e de vinho de videiras consorciadas com plantas de cobertura - Zalamena J. (2013)
The objective of this work was to evaluate the influence of green cover crops on vine productivity and on grape and wine composition. For two growing seasons, evaluations were done for three intercrops, two managements of the cover crops, and for a control treatment with weeds controlled by herbicides and mowing. A vineyard of 'Cabernet Sauvignon', located at 1,130 m altitude in a Haplumbrept soil, in São Joaquim, SC, Brazil was used. Intercropping was done with a succession of the cover crops moha (Setaria italica) with annual ryegrass (Lolium multiflorum), and buckwheat (Fagopyrum esculentum) with oat (Avena sativa), and with perennial fescue (Fetusca sp.). Cover crop managements consisted of transferring or not crop residues from the row to the between rows. Grape yield were higher in vines intercropped with the annual plants, in comparison to the control treatment or to fescue. The management of the cover crops did not affect the evaluated variables. Intercropping did not consistently influence N contents of grapes and wine composition; however, soluble solid contents of must were greater with intercropping treatments compared to control, in the last season. Moreover, vines intercropped with fescue can enable wine with greater content of anthocyanins and total polyphenols.